Bis{2-ethoxy-6-[2-(ethylammonio)ethyliminomethyl]phenolato}thiocyanatozinc(II) nitrate - Guo, Hui-Rui (International Union of Crystallography, 2008)
The title complex, [Zn(NCS)(C(13)H(20)N(2)O(2))(2)]NO(3), consists of a complex mononuclear Zn(II) cation and a nitrate counter-anion. The Zn(II) ion is five-coordinate in a trigonal-bipyramidal geometry. The thiocyanate N atom and two O atoms from two Schiff bases define the equatorial plane, and the two imine N atoms from the same two Schiff bases occupy the axial positions, with an N—Zn—N angle of 175.98 (7)°. The amine N atoms of the Schiff base ligands are protonated and are not involved in the coordination to the metal. The dihedral angle between the two substituted benzene rings is 87.7 (2)°. The nitrate counter-ions are linked to the cations through N—H⋯O hydrogen bonds.